2008
DOI: 10.1126/science.1154069
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Fold Localization in Thin Elastic Membranes

Abstract: Thin elastic membranes supported on a much softer elastic solid or a fluid deviate from their flat geometries upon compression. We demonstrate that periodic wrinkling is only one possible solution for such strained membranes. Folds, which involve highly localized curvature, appear whenever the membrane is compressed beyond a third of its initial wrinkle wavelength. Eventually the surface transforms into a symmetry-broken state with flat regions of membrane coexisting with locally folded points, reminiscent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

42
587
7
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 493 publications
(637 citation statements)
references
References 25 publications
42
587
7
1
Order By: Relevance
“…Larger applied strain forces these wrinkles merge into a single fold (Figure 1 d), while the surrounding gold fi lm is intact. [15][16][17] Sub-millimeter thick membranes of PU foam are produced using a simple bar coater setup ( Figure 2 a). A variety of two-component systems are available to produce PU foams, allowing for a wide range of foam densities and morphologies.…”
Section: Localization Of Folds and Cracks In Thin Metal Films Coated mentioning
confidence: 99%
“…Larger applied strain forces these wrinkles merge into a single fold (Figure 1 d), while the surrounding gold fi lm is intact. [15][16][17] Sub-millimeter thick membranes of PU foam are produced using a simple bar coater setup ( Figure 2 a). A variety of two-component systems are available to produce PU foams, allowing for a wide range of foam densities and morphologies.…”
Section: Localization Of Folds and Cracks In Thin Metal Films Coated mentioning
confidence: 99%
“…For a thin elastic film supported on a viscous substrate, wrinkles lose their periodicity and transition to localized folds once the total confinement of the thin film approaches one third of the initial wrinkling wavelength [33,34] . The transition to localized deformation may even lead to the fracture of the film [35] .…”
Section: Introductionmentioning
confidence: 99%
“…44Ϫ48 It has been demonstrated that buckling and folding are not independent phenomena and wrinkles appear as a first order linear response to external or internal stresses. 49 Folding and crumpling of compliant structures result in localization of the strain energy into a network of ridges and sharp corners. 50Ϫ52 Herein, we report ultrathin (20Ϫ100 nm) gel films tethered to solid substrates which exhibit unusual spontaneous and regular self-folding under swelling induced compressive stresses.…”
mentioning
confidence: 99%